Marxism, colonialism, and cricket : C.L.R. James's Beyond a Boundary - Featherstone, David, 1974-; Gair, Christopher, 1961-; Høgsbjerg, Christian; Smith, Andrew, 1974- (C.L.R. James Archives (Series), 2018)
Widely regarded as one of the most important and influential sports books of all time, C.L.R. James's Beyond a Boundary is--among other things--a pioneering study of popular culture, an analysis of resistance to empire and racism, and a personal reflection on the history of colonialism and its effects in the Caribbean. More than fifty years after the publication of James's classic text, the contributors to Marxism, Colonialism, and Cricket investigate Beyond a Boundary's production and reception and its implication for debates about sports, gender, aesthetics, race, popular culture, politics, imperialism, and English and Caribbean identity. Including a previously unseen first draft of Beyond a Boundary's conclusion alongside contributions from James's key collaborator Selma James and from Michael Brearley, former captain of the English Test cricket team, Marxism, Colonialism, and Cricket provides a thorough and nuanced examination of James's groundbreaking work and its lasting impact.